Hybrid Air Conditioning in Vehicle - Asafrah, Rami; Hawareen (جامعة بوليتكنك فلسطين - ميكانيك, 2009)
The basic principle of the system utilizes the high pressure of the exhaust gases that is directed through a nozzle which increases the velocity of these gases. This high velocity gas is made to impinge on the turbine rotor which rotates at high speeds . this roto is coupled to the compressor of air conditioning system. In this project two compressors are to be used, one which connected to the engine by belt and the other which coupled to the turbine and driven by the exhaust gases. The power produced from the turbine will be calculated and decide if this power is enough to drive the air conditioning compressor or not. In this project a control is being used between the two compressors, the conventional compressor is used in high demand ( high load or at idle speed) but the other compressor is used in good condition ( high speed or at low load ).
no of pages 86, 24870, ميكانيك 14/2009 , in the store
Keywords: Vehicles - Hybrid Air Conditioning